UPAYA KEPALA SEKOLAH DALAM MENGEMBANGKAN KETRAMPILAN SISWA MELALUI TENUN IKAT PADA SMA KRISTEN LOLI KECAMATAN POLEN KABUPATEN TIMOR TENGAH SELATAN: UPAYA KEPALA SEKOLAH DALAM MENGEMBANGKAN KETRAMPILAN SISWA MELALUI TENUN IKAT - Baun, Soleman; Soinbala, Nusriwan Chr.; Fomeni, Melti; Tabun, Ayub (APOSTOLOS, 2024)
The purpose of this article is to discuss the Principal's Efforts in Developing Student Skills Through Ikat Weaving at Loli Christian High School, Polen District, North Central Timor Regency. The research method used is descriptive qualitative. The subjects in this research were school principals with teacher respondents and craftsmen students. Data collection techniques are interviews, documentation. The results show that the efforts of the school principal in developing student creativity through woven ikat have been carried out in accordance with the function and role of the school principal so that the handicrafts owned by the students can be developed properly.